Electrocardiographic Abnormalities in Cardiac Contusion: Experimental Study - O. V. Korpacheva; V. T. Dolgikh (Общая реаниматология)
Objective: to study the incidence and pattern of cardiac arrhythmias and other abnormalities in the early posttraumatic period of experimental cardiac contusion and to assess their contribution to death and the development of posttraumat-ic myocardial dysfunction.Materials and methods: experiments were carried out on non-inbred albino male rats anesthetized with sodium thiopental. An electrocardiogram, respiration rate, and left carotid blood pressure were recorded in the direct fashion. Cardiac contusion was reproduced by an original device that imitated a blow of the steering wheel to the anterior chest, as that observed when a moving car clashed against an obstacle. Some animals were traumatized after preadministration of atropine sulfate.Results: sinus bradycardia accompanied by bradypnoea or short-term apnoea and lowered blood pressure is a compulsory and persistent ECG abnormality. Preinjection of atropine significantly prevents the occurrence of these changes and points to the likely reflectory mechanism of their development. Other ECG abnormalities (heterotopic rhythms, premature beats, conduction blockade, terminal ventricular complex changes, etc.) are encountered in a variety of combinations, including those among which typical changes that are undetectable, are diverse, short-term, and labile. Among them, there are virtually no hemodynamic and potentially fatal arrhythmias.Conclusion: in experimental isolated cardiac contusion, the pattern of cardiac arrhythmias differs from that observed in the inpatient setting. Cardiac arrhythmias and other ECG abnormalities do not make a considerable contribution to a mortality rate under the conditions of this experiment since there are no hemodynamic ones.